Ruthenium Catalysts for Olefin Metathesis: Understanding the Boomerang Mechanism and Challenges Associated with Stereoselectivity - Bates, Jennifer M. (Université d'Ottawa / University of Ottawa, 2014)
Ruthenium-alkylidene catalysts are widely used in organic synthesis to generate new C=C bonds in a process known as olefin metathesis. Much research has been dedicated to examining the organometallic species responsible for this transformation, and understanding the benefits and limitations of current state-of-the-art catalysts allows for the design of new and more efficient alternatives. Over the past decade, a topic of much debate has been the so-called “boomerang” (or release-return) mechanism, and whether it operates in the Hoveyda catalysts. The ability of the styrenyl ether ligand, once released from the catalyst during initiation, to be recaptured by the vulnerable active species, has major implications in catalyst recyclability. Chapter 3 describes the use of a 13C-labeled styrenyl ether ligand, in conjunction with an unlabeled second-generation Hoveyda catalyst, to confirm the operation of this mechanism during catalysis. This study demonstrated that the labeled styrenyl ether ligand competes with the substrate for the four-coordinate active species: the labeled moiety rapidly incorporates into the Hoveyda catalyst during both ring-closing- and cross-metathesis examples. Chapter 4 focuses on addressing the selectivity challenges associated with olefin metathesis, particularly during RCM macrocyclization reactions where E/Z mixtures are typically obtained. Designing catalysts that can dictate and control the stereochemistry of a product mixture minimizes waste, and ultimately reduces cost by eliminating the need for separation techniques. A great deal of research has focused on constructing catalysts with ligands that can exert the appropriate steric pressure on a metallocyclobutane intermediate, in order to generate the desired Z-product. Chapter 4 of this thesis examined the ability of a Hoveyda- and Grubbs-type catalyst containing monothiolate ligands, to promote Z-selective RCM macrocyclization. Catalyst lifetimes were also examined, in addition to the impact of altering reaction conditions, specifically concentration, on product distribution. These experiments afford information that will aid in the design of improved catalysts for Z-selective RCM macrocyclization.
Keywords: Olefin Metathesis; Ruthenium; Catalyst